A role for PAK1 mediated phosphorylation of β-catenin Ser552 in the regulation of insulin secretion. Issue 8 (30th April 2021) - Sorrenson, Brie; Dissanayake, Waruni C.; Hu, Fengyun; Lee, Kate L.; Shepherd, Peter R.
Abstract : The presence of adherens junctions and the associated protein β-catenin are requirements for the development of glucose-stimulated insulin secretion (GSIS) in β-cells. Evidence indicates that modulation of β-catenin function in response to changes in glucose levels can modulate the levels of insulin secretion from β-cells but the role of β-catenin phosphorylation in this process has not been established. We find that a Ser552Ala version of β-catenin attenuates glucose-stimulated insulin secretion indicating a functional role for Ser552 phosphorylation of β-catenin in insulin secretion. This is associated with alterations F/G actin ratio but not the transcriptional activity of β-catenin. Both glucose and GLP-1 stimulated phosphorylation of the serine 552 residue on β-catenin. We investigated the possibility that an EPAC-PAK1 pathway might be involved in this phosphorylation event. We find that reduction in PAK1 levels using siRNA attenuates both glucose and GLP-1 stimulated phosphorylation of β-catenin Ser552 and the effects of these on insulin secretion in β-cell models. Furthermore, both the EPAC inhibitor ESI-09 and the PAK1 inhibitor IPA3 do the same in both β-cell models and mouse islets. Together this identifies phosphorylation of β-catenin at Ser552 as part of a cell signalling mechanism linking nutrient and hormonal regulation of β-catenin to modulation of insulin secretory capacity of β-cells and indicates this phosphorylation event is regulated downstream of EPAC and PAK1 in β-cells.